2020
DOI: 10.3390/v12010095
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Clinical Definitions of Influenza for Public Health Surveillance Purposes

Abstract: This study investigated the performance of various case definitions and influenza symptoms in a primary healthcare sentinel surveillance system. A retrospective study of the clinical and epidemiological characteristics of the cases reported by a primary healthcare sentinel surveillance network for eleven years in Catalonia was conducted. Crude and adjusted diagnostic odds ratios (aDORs) and 95% confidence intervals (CIs) of the case definitions and symptoms for all weeks and epidemic weeks were estimated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…These results suggest that, for both SARS-CoV-2 and other commonly diagnosed respiratory viral infections, the presenting symptoms at the time of the test order may not provide sufficient information to correctly classify whether a given patient will test positive for that virus. Prior studies of presenting symptoms and case definitions for influenza found that information on presenting symptoms alone is not sufficient to accurately diagnose influenza, or distinguish it from other influenza-like illnesses [8][9][10][11][12] , and our results support this finding. Though our Influenza Virus A model had one of the higher AUROCs we observed, it is not sufficient for use in a clinical setting.…”
Section: Resultssupporting
confidence: 65%
“…These results suggest that, for both SARS-CoV-2 and other commonly diagnosed respiratory viral infections, the presenting symptoms at the time of the test order may not provide sufficient information to correctly classify whether a given patient will test positive for that virus. Prior studies of presenting symptoms and case definitions for influenza found that information on presenting symptoms alone is not sufficient to accurately diagnose influenza, or distinguish it from other influenza-like illnesses [8][9][10][11][12] , and our results support this finding. Though our Influenza Virus A model had one of the higher AUROCs we observed, it is not sufficient for use in a clinical setting.…”
Section: Resultssupporting
confidence: 65%
“…No differences in the performance of the case definition or symptoms in influenza cases according to virus type were found in a recently published study [14]. The identified influenza virus sub-types were as following ( n = 7, 955): A/H1N1, 57%; B/Victoria, 17%; A/H3, 16%; B/Yamagata, 9% and B unidentified, 1%.…”
Section: Discussionmentioning
confidence: 85%
“…First, we modified the definition of influenza‐like illness in our eligibility criteria: fever and at least one of the three respiratory symptoms. Fever was deemed a powerful predictor of influenza virus infection in the past (OR: 3.47 to 4.03) 37,38 . However, Smith et al noted that patients with afebrile influenza virus infection had fewer respiratory symptoms 39 .…”
Section: Discussionmentioning
confidence: 99%